Nuclear reactor simulator in real time - Cuya, Teobaldo (2002)
Numerical methods are present to solve space-independent transport equations for 6 delayed neutron groups and the isotopic evolution of poisons produced in a reactor, as well as their implementation in the development of a real time nuclear reactor simulator. An asymptotic performance is assumed for the spatial component of the neutron flux. The inhour equation, the control and safety rod effect, the reactivity transients and an interface to help the user become familiar with the setting, were considered to develop the simulator. An access routine to the PC timer has been developed to make the simulator work in real time.